Luke's Jesus in the Roman Empire and the emperor in the Gospel of Luke - Seo, Pyung Soo (JSTOR EBA., 2015)
Shrewd and thoughtful, Pyung-Soo Seo offers a refreshing perspective on Luke's Gospel, which provides valuable clues to a deeper understanding of the vast power of the Roman Empire through Jesus' birth and trial accounts.